2016
DOI: 10.1088/1367-2630/18/11/113022
|View full text |Cite
|
Sign up to set email alerts
|

Submonolayer and multilayer growth of titaniumoxide-phthalocyanine on Ag(111)

Abstract: For exploiting the full potential of organic materials for future organic electronic devices it is of crucial importance to understand structural and electronic properties of metal-organic interfaces and adsorbate systems, in particular electronic interactions and growth mechanisms. Phthalocyanine molecules represent one class of materials which are very frequently discussed in this context. They feature an appealing tunability in terms of structural, electronic and magnetic properties, simply by exchanging th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
65
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 63 publications
(129 reference statements)
12
65
1
Order By: Relevance
“…An f -LUMO is expected on Cu(110) as well since this surface is both more reactive and has a lower work function (∼200 meV) relative to Ag(111). Each of these factors shifts the LUMO further below E F , thus supporting our assignment [24,[37][38][39]. The accompanying STM image [ Fig.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…An f -LUMO is expected on Cu(110) as well since this surface is both more reactive and has a lower work function (∼200 meV) relative to Ag(111). Each of these factors shifts the LUMO further below E F , thus supporting our assignment [24,[37][38][39]. The accompanying STM image [ Fig.…”
Section: Resultssupporting
confidence: 82%
“…5(c) and 6(b)]. Again, a partially filled f -LUMO for TiOPc on Cu(110) is expected given reports of an f -LUMO for TiOPc and CuPc on Ag(111) [37], and other phthalocyanines on Cu(110) [52]. Charge flow out of the surface and into the molecule counteracts pushback effects, and equilibrium is reached at ϕ ads = −400 meV for 1-ML coverage.…”
Section: Discussionmentioning
confidence: 60%
“…[38,41] Previous SPA-LEED studies of TiOPc on Ag(111) by Fernández et al have shown that this arrangement results in a POL-phase for the monolayer with a primitive unit cell of A uc = 199 Å 2 , [37] while the bilayer is somewhat compressed and has a unit cell area of 189 Å 2 . [38,41] Previous SPA-LEED studies of TiOPc on Ag(111) by Fernández et al have shown that this arrangement results in a POL-phase for the monolayer with a primitive unit cell of A uc = 199 Å 2 , [37] while the bilayer is somewhat compressed and has a unit cell area of 189 Å 2 .…”
Section: Polar Phthalocyaninesmentioning
confidence: 95%
“…[38,41] Previous SPA-LEED studies of TiOPc on Ag(111) by Fernández et al have shown that this arrangement results in a POL-phase for the monolayer with a primitive unit cell of A uc = 199 Å 2 , [37] while the bilayer is somewhat compressed and has a unit cell area of 189 Å 2 . [41] It is noteworthy that especially for the case of polar phthalocyanines, post-annealing at around 480 K after each deposition step is important in order to obtain reproducible Φ values and long-range ordered films. For both substrates, four different regimes can be identified.…”
Section: Polar Phthalocyaninesmentioning
confidence: 95%
See 1 more Smart Citation